Near complete genome assembly of Yadong trout (Salmo trutta) - Chen Li; Shenglei Han; Shuo Li; Kaiqiang Liu; Yuyan Liu; Hong-yan Wang; Qian Wang; Changlin Liu; Changwei Shao (Scientific Data)
Abstract The Yadong trout (Salmo trutta), a species endemic to the Yatung River in Tibet, China, was classified as a second-class protected species in the 20th century. Now, it is considered one of the most important fishery resources in China. In this study, we assembled a near-complete genome of the S. trutta, integrating PacBio HiFi, Hi-C, and ONT sequencing technologies. The genome assembly spans 2.49 Gb, with 96.87% of the sequence anchored onto 40 chromosomes. In this assembly, a total of 12 chromosomes were assembled to a gap-free level, with 8 of them reaching the telomere-to-telomere level. The completeness of this assembly was assessed at 99.50% by BUSCO, containing approximately 63.24% repetitive sequences, and predicted to encode 41,782 protein-coding genes. This is the first near-complete genome assembly of the S. trutta, providing an essential resource for molecular breeding and germplasm conservation of this important species.